Контроль працездатності когенераційної системи на пелетному паливі - Чайковська, Євгенія Євстафіївна (НТУ "ХПІ", 2017)
Запропонована інтегрована система підтримки температури місцевої води при вимірюванні температури газів та температури зворотної води на вході в теплообмінник другого контуру когенераційної системи. Прийняття рішень на зміну кількості пластин теплообмінника надає можливість підтримувати співвідношення виробництва електричної енергії та теплоти при використанні зміни частоти обертання електродвигуна повітряного вентилятора щодо зміни витрати повітря, що подається на підігрів, для сушки деревини. Такий підхід дозволяє, наприклад, в умовах функціонування когенераційної системи потужністю 115 кВт знизити собівартість виробленої енергії до 20-30 %.

The proposed architecture of the cogeneration system, which is the basis integrated dynamic subsystem - cogeneration plant, heat exchanger secondary circuit heating local water, drying plant, heat exchanger heating the air, the air blower and blocks a charge, discharge, assessment of functional performance that are agreed upon interaction with dynamic subsystem. Complex mathematical modeling of the dynamics of the second circuit of the heat exchanger cogeneration system provides the ability to define tolerances to temperature change local water levels established for the operation. A complex mathematical and logical modeling efficiency cogeneration control system for obtaining functional evaluation of local water temperature changes. Block diagram of temperature maintenance of local water-level decision-making to determine the final information on the decision to change the number plates of the heat exchanger by comparing the temperature of the gases at the inlet to the heat exchanger of the second circuit cogeneration system, measured from the reference value. The proposed integrated system of support for local water temperature for measuring the temperature of gases and return water temperature at the inlet to the heat exchanger of the second circuit of the cogeneration system. Deciding to change the number plate heat exchanger allows to maintain the ratio of production of electricity and heat using changes of rotational speed of the electric fan of air to change the air flow supplied to the heater for drying wood. This approach allows, for example, in terms of functioning cogeneration system capacity of 115 kW reduce the cost of energy produced (20-30) %.
Control working ability of the cogeneration system on pellet fuel
Keywords: когенераційна установка; прийняття рішень; система підтримки температури; електрична енергія; cogeneration plant; control of operation; making decisions